A systematic review of measures of adherence to physical exercise recommendations in people with stroke. (March 2019) - Levy, Tamina; Laver, Kate; Killington, Maggie; Lannin, Natasha; Crotty, Maria
Objective: To review methods for measuring adherence to exercise or physical activity practice recommendations in the stroke population and evaluate measurement properties of identified tools. Data sources: Two systematic searches were conducted in eight databases (MEDLINE, CINAHL, PsycINFO, Cochrane Library of Systematic Reviews, Sports Discus, PEDro, PubMed and EMBASE). Phase 1 was conducted to identify measures. Phase 2 was conducted to identify studies investigating properties of these measures. Review methods: Phase 1 articles were selected if they were published in English, included participants with stroke, quantified adherence to exercise or physical activity recommendations, were patient or clinician reported, were defined and reproducible measures and included patients >18 years old. In phase 2, articles were included if they explored psychometric properties of the identified tools. Included articles were screened based on title/abstract and full-text review by two independent reviewers. Results: In phase 1, seven methods of adherence measurement were identified, including logbooks ( n = 16), diaries ( n = 18), 'record of practice' ( n = 3), journals ( n = 1), surveys ( n = 2) and questionnaires ( n = 4). One measurement tool was identified, the Physical Activity Scale for Individuals with Physical Disabilities ( n = 4). In phase 2, no eligible studies were identified. Conclusion: There is not a consistent measure of adherence that is currently utilized. Diaries and logbooks are the most frequently utilized tools.